PENGARUH CITRA MEREK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA AVANZA DALAM KONDISI PANDEMI COVIT 19 DI KECAMATAN MEDAN TUNTUNGAN : ( Studi Kasus : Masyarakat Pembeli Mobil Avanza di Kecamatan Medan Tuntungan) - Simanihuruk, Peran; Munthe, Kornel; Manihuruk, Yunika Lucianna (Jurnal Manajemen dan Bisnis, 2022)
The purpose of the study was to analyze the effect of brand image, price and promotion on the decision to purchase a Toyota Avanza in the conditions of the COVID-19 pandemic in Medan Tuntungan District. The number of samples is 96 respondents, collecting data with questionnaires and documentation, using descriptive analysis and multiple linear regression analysis methods and testing hypotheses using t-test and F-test. The results showed that the brand image variable with an average mean = 4.23. The mean range is in the agree (S) category with strongly agree (SS) meaning that the respondents are more dominant in stating that the Toyota Avanza brand image is very good. Variable Price mean mean = 4.25 . The range mean is in the agree category (S) with strongly agree (SS) meaning that the respondent is more dominant in stating the price of the Toyota Avanza is in accordance with the expected quality. Promotion Variable with mean = 4.23 . The mean range is in the agree category (S) with strongly agree (SS) meaning that the respondents are more dominant in stating that the promotion carried out by Toyota has been very good. Purchasing decision variable with average mean = 4.26. The mean range is in the agree category (S) with strongly agree (SS) meaning that the respondents are more dominant in stating that the purchasing decisions made are as expected. Multiple regression equation: KP = 0.485 + 0.341CM + 0.335H + 0.404P, t.counting brand image = 3.417, t.counting price = 3.377 and t.counting promotion = 5.827, F.counting = 29.842 and R2 = 0.510. This means that brand image, price and promotion have a positive influence on purchasing decisions. However, the one that has a greater influence on purchasing decisions is the promotion variable. With the F test there is F count = 29,842 > F table, then Ho is rejected and H4 is accepted. This means that the variables of brand image, price, and promotion simultaneously have a significant effect on the Purchasing Decision variable. With the t test, that the t count (brand image, price, and promotion) is greater than the t table, Ho is rejected and H1, H2 and H3 are accepted. This means that the brand image, price, and promotion variables partially have a significant effect on the Purchase Decision variable. The R2 value of 0.510 means that 51% of the purchasing decision variables can be explained by the brand image, price, and promotion variables and the remaining 49% is influenced by other variables outside the independent variables in this study. The lowest assessment of respondents' responses about promotions regarding gift offers makes consumers interested in buying a toyota avanza car. So it is better to review the gift offer to attract consumers by using a pricing strategy to attract consumers, for example: giving a discount. The lowest assessment of respondents' responses to the price regarding the price of the toyota avanza is commensurate with the quality given. It is hoped that the company can provide additional features in the toyota avanza such as the addition of car accessories. Future researchers should be more careful in selecting respondents. We recommend that you look for respondents who have used Toyota products, then look for a more comfortable place if you are looking for respondents, when respondents fill out questionnaires, researchers give intensive attention to respondents so as not to give careless answers to the questionnaire.